Microalgae blending for sustainable metallurgical coke production – Impacts on coking behaviour and coke quality. (15th July 2023) - Jayasekara, Apsara S.; Brooks, Brody; Steel, Karen; Koshy, Pramod; Hockings, Kim; Tahmasebi, Arash
Highlights: Impact of microalgae blending on coking behaviour and coke quality is study. Microalgae addition of up to 10% did not adversely influence coal thermoplasticity. Microalgae addition lowered the activation energy of carbonization in the plastic range. Porous biochar structures, typical of conventional biomass, were not detected for microalgae. Cokes made from blends of microalgae and coal outperformed those of conventional biomass. Abstract: The steel industry is responsible for approximately 7% of global greenhouse gas emissions, mainly in the form of CO2 from the blast furnace ironmaking process. Among several strategies proposed to reduce CO2 emission, the partial replacement of coal with biomass during the cokemaking process has gained increasing interest. However, such replacement with lignocellulosic biomass species demonstrates a detrimental effect on coke quality. In this work, as an alternative to lignocellulosic biomass, the use of microalgae biomass ( Chlorella vulgaris ) is discussed for coal blending and bio-coke production. Three Australian metallurgical coal samples, varying in rank and fluidity, were blended with microalgae at up to 10 wt% to evaluate the impact of biomass addition rate on coking behaviour and coke quality. The work evaluates the impact of microalgae on coal blend properties, coking performance, and coke quality and strength (CSR/CRI, microtexture, and coke reactivity). The results demonstrated that microalgae blending with high-rank premium metallurgical coals did not adversely affect thermoplastic properties during coking or resultant bio-coke quality. Furthermore, the reactivity under simulated blast furnace conditions showed that microalgae addition led to a slight increase of up to 4.4% in coke gasification reactivity, which was attributed to the higher alkali content and isotropic textures in coke. Unlike lignocellulosic biomass, in bio-cokes produced by blending microalgae no porous and fibrous structures related to the biochar structure were identified. It was postulated that this non-fibrous nature of microalgae allows cokes to maintain their strength even for blending up to 10 wt%.